2016
DOI: 10.19030/jabr.v32i4.9729
|View full text |Cite
|
Sign up to set email alerts
|

Understanding The Typical Vacations Of U.S. Southern Travelers

Abstract: This paper investigates important factors associated with vacation decisions made for typical vacations by U.S. southern travelers, an area given minimal focus in the marketing tourism literature. The paper effectively identifies key vacation influences to leisure travel which include distance, group size, vacation length, lead time, education level, income level, and age.  Additionally, the paper identifies nine unique types of southern vacation travelers using a cluster analysis approach. Ultimately, the pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The study looked at a time horizon between 1 and 12 months, mainly corresponding with a study by Hill (2016), who found that 91.5% of all respondents had a planning time varying between 2 weeks and 12 months. To determine which lag is relevant, the author applied a Stepwise Least Squares Estimation procedure, using the combinatorial method.…”
Section: Coinciding or Lagged Relationshipsmentioning
confidence: 99%
“…The study looked at a time horizon between 1 and 12 months, mainly corresponding with a study by Hill (2016), who found that 91.5% of all respondents had a planning time varying between 2 weeks and 12 months. To determine which lag is relevant, the author applied a Stepwise Least Squares Estimation procedure, using the combinatorial method.…”
Section: Coinciding or Lagged Relationshipsmentioning
confidence: 99%